PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, UKURAN DEWAN KOMISARIS, LEVERAGE DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (Studi kasus pada Perusahaan Manufaktur yang terdaftar di BEI pada Tahun 2014-2016) - Wahyudiastutik, 15.05.62.0014; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
The purposes of this research are to analyze and test the influence of companyâs external and internal variables with disclosure of CSR at manufacturing companies which listed in Bursa Efek Indonesia on 2014-2017. The ratio that used in the research are the measure of company, profitability, the measure of board commissioners, leverage and liquidity.Â The method of this research is purposive sampling. The samples are 60 manufacturing companies which taken periodically. Multiple linear regression is used for analyzing the influence of independent variable to dependent variable. The tests of hypothesis are using f test and t test with 5% significance.Â The result of determinant coefficient test is 75.1% CSR which can explained by the measure of company, profitability, the measure of board commissioners, leverage and liquidity. Meanwhile 24.9% CSR is explained by the other factor in the other variable. The result of t test is the measure of company and profitability variable are influenced to CSR and the measure of board commissioners, leverage and liquidity arenât.Keywords:Â The Measure of Company, Profitability, The Measure of Board Commissioners, Leverage and Liquidity, Corporate Social Responsibility